Iterated function system of locally contractive operators - Petruşel, Adrian (Rev. Anal. Numér. Théor. Approx., 2004)
The aim of this paper is to study the properties of the fractal and the multi-fractal operator generated by some iterated function system satisfying to a locally contractive type condition.